ORISINALITAS AL-QUR’AN MENURUT PANDANGAN ORIENTALIS ( STUDI ANALISIS PEMIKIRAN TOSHIHIKO ISUTZU, ANDHREW RIPPIN DAN ANGELIKA NEUWIRTH) (EL-MAQRA', 2024)
This article aims to provide a conceptual overview regarding orientalist thought towards the Koran which is in line with the thinking of Muslims in general. In this process, the authors apply qualitative data analysis based on library research through the steps of textual analysis and historical and dynamic contextual interpretation of orientalist thought which is in line with the thinking of Muslims in general. Through this analytical procedure, the author reveals that if the researchers previously examined non-Muslim orientalists who did not believe in the authenticity of the Al-Qu'an and the history of the revelation of the Qur'an. In contrast to the findings of the authors in this article, it shows that there are some non-Muslim orientalists who acknowledge the authenticity of the Qur’an and the history of the revelation of the Qur’an, although these thoughts are not immune to objections by orientalists or other scholars.